Pengaruh Terapi Bermain Dengan Media Scrapbook Terhadap Kecemasan Anak Usia Prasekolah Yang Mengalami Hospitalisasi - Malita, Malita; Dekawaty, Ayu; Suzanna, Suzanna (Penerbit Goodwood, 2024)
Purpose: This study aimed to determine the effect of play therapy with scrapbook media on anxiety in preschool-aged children hospitalized at Muhammadiyah Hospital Palembang. Research Method: This study used a pre-experimental method with a one-group pretest and post-test design. Purposive sampling was used with 16 respondents who were pediatric patients treated at Muhammadiyah Hospital Palembang. The intervention was provided for 30 min, once a day, during the child's free time. Results: The results of the non-parametric test using the Wilcoxon Test showed a p-value <0.000 (<0.05). Limitations: This study involved only 16 respondents, which limits the generalizability of the findings. Larger sample sizes would provide more robust and reliable results. Contributions: This article contributes to the growing body of evidence supporting play therapy as an effective tool for managing anxiety in preschool-aged children, particularly in hospital settings.